CRIMINOLOGÍA ACADÉMICA EN LA FACULTAD DE CIENCIAS JURÍDICAS Y POLÍTICAS DE LA UNIVERSIDAD NACIONAL DEL ALTIPLANO DE PUNO - Espinoza Coila, Michael (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2020)
This article explains how it came to be, how it was, and what we expect from academic Criminology at the Professional Law School of the Universidad Nacional del Altiplano de Puno after the bicentennial of Peru, and we conclude that academic criminology was developed in the Faculty of Jurisprudence of the National University of San Carlos de Puno, it was formally created as a course in the Faculty of Legal and Political Sciences of the National University of the Altiplano of Puno, it was a traditional content course dedicated to etiology, progressively it developed a biospisosocial criminology of the crime and we hope that Criminology after the bicentennial of Peru, has a critical and precautionary content that allows the construction of a regional criminological knowledge capable of understanding the reality of Peru and Puno, for the prevention of genocide and massacres, and the containment of punitive power.